Reforming the Legal Regulation of the Indonesian National Armed Forces’ Involvement in Handling National Cyber Threats Based on Legal Certainty and Democratic Rule of Law Principles - Agusra Yendri; Zainal Arifin Hoesein (SULTAN ADAM: Jurnal Hukum dan Sosial, 2026)
The development of information technology has given rise to cyber threats as a form of non-conventional threat that has the potential to disrupt national sovereignty, security, and defense. This study seeks to analyze the legal framework of the Indonesian National Armed Forces' involvement in responding to national cyber threats, assess the extent to which the current framework provides legal certainty, and develop recommendations for legal reform consistent with the principles of legal certainty and a democratic rule-of-law state. The research method employed is normative juridical, with both legislative and conceptual approaches. The results indicate that current legal regulations do not explicitly address cyber threats as a national defense threat, do not provide a legal definition of cyber warfare, and do not clearly define the limits of the Indonesian National Armed Forces' authority in cyber defense operations. This situation creates a legal vacuum, overlapping authority between institutions, and legal uncertainty in addressing national cyber threats. Legal reform is needed through the reconstruction of regulations governing cyber threats as a national defense threat, affirmation of the Indonesian National Armed Forces' authority in cyber defense operations, strengthening inter-institutional coordination mechanisms, and establishing a system of oversight and accountability that guarantees the protection of human rights and the principle of civil supremacy in a democratic state governed by the rule of law.